Catalysts for hydrogenation and dehydrogenation of organic hydrogen storage liquids, methods of making and using same
Patent Information
- Application Number
- CN202611133942.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-30
AI Technical Summary
但是该方法制备的催化剂铂含量相对较高(>3wt%)
(1)本申请通过化学修饰的方法在催化剂载体表面形成涂层,涂层上的有机官能团极大增强了对活性组分的锚定作用,并在载体和金属活性组分之间建立强化学键,抑制活性组分在催化剂上的迁移、团聚及过度生长,从而获得尺寸更小、分散更均匀的金属纳米颗粒。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This application relates to the field of hydrogen storage technology, specifically to a catalyst for hydrogenation and dehydrogenation of organic hydrogen storage liquids, its preparation method, and its application. Background Technology
[0002] With rapid global industrialization, human demand for traditional fossil fuels such as coal, oil, and natural gas has been continuously increasing, leading to a surge in carbon dioxide emissions and triggering the greenhouse effect. This has caused immense damage to the Earth's ecosystem, and the problem of environmental degradation is becoming increasingly severe. Shifting the energy structure from traditional fossil fuels to clean energy is urgent. In this transition, traditional coal-fired power plants will gradually be relegated to auxiliary power sources, while the proportion of clean energy sources such as wind and solar power will gradually increase. However, renewable energy sources such as wind and solar power are intermittent and fluctuating, resulting in significant power instability in their power systems. Therefore, it is necessary to develop energy storage systems that correspond to this energy transformation.
[0003] Hydrogen energy, as a clean secondary energy source, boasts advantages such as abundant supply, high calorific value, and high conversion rate, and is widely used in fuel cells, hydrogen refueling reactions, and other technological fields. Developing hydrogen-electric coupling technology is a crucial step in ensuring stable energy output. However, due to the unique physicochemical properties of hydrogen, its storage and transportation have always been major technological barriers hindering the large-scale development and utilization of hydrogen energy. Currently, global hydrogen storage technologies mainly include high-pressure gaseous hydrogen storage, cryogenic liquid hydrogen storage, solid-material hydrogen storage, and organic liquid hydrogen storage. Among these, organic liquid hydrogen storage technology utilizes reversible addition and dehydrogenation reactions of unsaturated organic liquids to achieve hydrogen storage and release. It offers advantages such as technical safety, high hydrogen storage density, and full utilization of existing oil and gas transportation and storage petrochemical infrastructure, enabling large-scale, long-distance transportation of hydrogen at ambient temperature and pressure.
[0004] The core of organic liquid hydrogen storage technology lies in the catalyst. Selecting a suitable catalyst can effectively lower the barrier to hydrogenation and dehydrogenation reactions, reducing the difficulty of the reaction. Currently, organic liquid hydrogen storage catalysts can be divided into two main categories: noble metal catalysts and non-noble metal catalysts. Among them, noble metal catalysts are mainly composed of noble metals such as Pt, Pd, Ru, and Rh, or are mainly noble metal catalysts with a small amount of additives, and the noble metal loading is high (>1wt%). Their high cost limits the industrialization of organic liquid hydrogen storage. Therefore, designing a catalyst that reduces cost while ensuring catalytic activity is the key to synthesizing organic liquid hydrogen storage catalysts.
[0005] CN113368897B reports a highly active alumina-supported platinum-based catalyst, its preparation method, and its application. The method involves pretreating the alumina support with organic atmosphere dielectric barrier discharge plasma to obtain an alumina support grafted with organic groups. Platinum is then loaded onto the organic alumina support via impregnation to obtain a highly active alumina-supported platinum catalyst. However, the catalyst prepared by this method has a relatively high platinum content (>3 wt%). Summary of the Invention
[0006] To address the aforementioned technical problems, this application provides a catalyst for hydrogenation and dehydrogenation of organic hydrogen storage liquids, its preparation method, and its application. The catalyst provided in this application exhibits high dispersibility, excellent anti-agglomeration properties, and a low loss rate of active components, achieving excellent catalytic hydrogenation and dehydrogenation activity even with low precious metal content.
[0007] In a first aspect, this application provides a catalyst for hydrogenation and dehydrogenation of organic hydrogen storage liquids, comprising a metal oxide support, an organic composite layer supported on the metal oxide support, and a metal active component combined with the organic composite layer. The organic composite layer comprises a first organic component containing phenolic hydroxyl groups and a second organic component containing amine groups.
[0008] The catalyst of this application modifies the catalyst support by introducing organic functional groups, thereby altering the charge distribution on the support surface and forming a composite layer on the catalyst support substrate. The organic functional groups introduced into the composite layer self-assemble to form a cross-linked porous framework. This framework can capture and coordinate metal ions through phenolic hydroxyl groups, thus anchoring the metal active centers and improving the dispersion of active centers on the catalyst support surface. Simultaneously, the small molecule hydroxyl groups contained in the first organic component of the composite layer can penetrate into the micropores to anchor the internal metal, while the second organic component constructs a binding layer on the surface of mesopores / particles, resulting in a uniform distribution of metal inside and outside the pores and a significantly higher dispersion of active centers compared to a single component. The first organic component can simultaneously reduce noble and non-noble metals under low-temperature conditions, avoiding preferential reduction and phase separation of noble metals. The second organic component can construct a three-dimensional nitrogen-carbon framework, neutralize the acidity of the support, and inhibit particle agglomeration and carbon deposition rates. The combined effect of these two components simultaneously enhances the activity and stability of the catalyst of this application.
[0009] In some embodiments, the first organic component is selected from one or more polyphenolic compounds and their derivatives. In some embodiments, the polyphenolic compound is selected from one or more of tannic acid, 3,4,5-trihydroxybenzoic acid, pyrogallol, 2,2',4,4'-biphenyltetrol, black thorn bark condensed tannin, and lignin sulfonate. In some embodiments, the polyphenolic compound is selected from tannic acid.
[0010] In some embodiments, the second organic component is selected from one or more polyamine polymers and their derivatives. In some embodiments, the polyamine polymer is selected from one or more polyethyleneimine, polyallylamine hydrochloride, polypropyleneimine, and aminolignin. In some embodiments, the polyamine polymer is selected from polyethyleneimine.
[0011] In some embodiments, the second organic compound containing an amino group is selected from one or more alkylene polyamines and their derivatives. In some embodiments, the alkylene polyamine is selected from one or more alkylene polyamines having 2 to 6 carbon atoms. In some embodiments, the alkylene polyamine is selected from one or more diethylenetriamine, triethylenetetramine, ethylenediamine, and hexamethylenediamine.
[0012] In some embodiments, the metal oxide support is selected from one or more of alumina supports, titanium oxide supports, cerium oxide supports, and porous molecular sieve supports. In some embodiments, the porous molecular sieve support is selected from two-dimensional porous molecular sieve supports. In some embodiments, the metal oxide support is selected from alumina supports. In some embodiments, the metal oxide support is selected from porous molecular sieve supports. In some embodiments, the porous molecular sieve support is selected from one or more of USY molecular sieve supports, Beta molecular sieve supports, and SBA-15 molecular sieve supports.
[0013] In some embodiments, the active metal component includes one or more of noble metals and optional non-noble metals.
[0014] In some embodiments, the precious metal is selected from one or more of platinum, ruthenium, rhodium, and palladium. In some embodiments, the precious metal is selected from platinum.
[0015] In some embodiments, the non-precious metal is selected from one or more of nickel, cobalt, copper, iron, and molybdenum. In some embodiments, the non-precious metal is selected from nickel.
[0016] In some embodiments, the active metal component includes nickel and platinum.
[0017] In some embodiments, the organic composite layer comprises a three-dimensional network structure formed by the self-assembly of the first organic component and the second organic component. In some embodiments, the three-dimensional network is formed by the self-assembly of the first organic component and the second organic component through one or more of hydrogen bonding, lone pair electron coordination, and oxygen coordination chelation.
[0018] In some embodiments, the three-dimensional network is selected from organic amine networks and / or metal polyphenol networks.
[0019] In some embodiments, the first organic component is bridged and anchored to the surface of the metal oxide carrier via the second organic component.
[0020] In some embodiments, the metal active component is bonded to the organic composite layer via chemical bonds. In other embodiments, the metal active component is bonded to the organic composite layer via metal-phenolic hydroxyl coordination bonds.
[0021] In some embodiments, the mass content of the metal active component is 0.01%-15% based on the mass of the catalyst, for example, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.3%, 3.5%, 3.7%, 4.0%, 4.3%, 4.5%, 4.7%, 5.0%, 5.3%, 5.5%, 5.7%, 6.0%, 6.3%, 6.5%, 6.7%, 7.0%, 7.3%, 7.5%, 7.7%, 8.0%, 8.3%, 8.5%, 9.0%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, or any value between them. In some embodiments, the mass content of the metal active component is 0.5%-10% based on the mass of the catalyst. In some embodiments, the mass content of the metal active component is 3%-8% based on the mass of the catalyst.
[0022] In some embodiments, the precious metal content is 0.1%-1.0% by mass, based on the mass of the catalyst, for example, 0.15%, 0.2%, 0.23%, 0.25%, 0.27%, 0.3%, 0.33%, 0.35%, 0.37%, 0.4%, 0.43%, 0.45%, 0.47%, 0.5%, 0.53%, 0.55%, 0.57%, 0.6%, 0.63%, 0.65%, 0.67%, 0.7%, 0.73%, 0.75%, 0.77%, 0.8%, 0.83%, 0.85%, 0.9%, 0.95%, or any value between them. In some embodiments, the precious metal content is 0.2%-0.8% by mass, based on the mass of the catalyst.
[0023] In some embodiments, the non-precious metal content is 1%-15% by mass, based on the mass of the catalyst, for example, 1.5%, 2.0%, 2.5%, 3.0%, 3.3%, 3.5%, 3.7%, 4.0%, 4.3%, 4.5%, 4.7%, 5.0%, 5.3%, 5.5%, 5.7%, 6.0%, 6.3%, 6.5%, 6.7%, 7.0%, 7.3%, 7.5%, 7.7%, 8.0%, 8.3%, 8.5%, 9.0%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, or any value between them. In some embodiments, the non-precious metal content is 3%-10% by mass, based on the mass of the catalyst.
[0024] In some embodiments, the mass ratio of the first organic component and the second organic component in the organic composite layer is from 1:0.1 to 1:4, for example, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.55, 1:0.6, 1:0.65, 1:0.7, 1:0.75, 1:0.8, 1:0.83, 1:0.85, 1:0.87, 1:0.9, 1:0.93, 1:0.95, 1:0.97, 1:1, 1:1.03, 1:1.05, 1:1.07, 1:1.1, 1:1.13, 1:1.15, 1:1.17, 1... The ratios are 1:1.2, 1:1.23, 1:1.25, 1:1.27, 1:1.3, 1:1.33, 1:1.35, 1:1.37, 1:1.4, 1:1.43, 1:1.45, 1:1.47, 1:1.5, 1:1.53, 1:1.55, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9, 1:3, 1:3.3, 1:3.5, 1:3.7, or any value between them. In some embodiments, the mass ratio of the first organic component and the second organic component in the organic complex layer is from 1:0.5 to 1:3. In some embodiments, the mass ratio of the first organic component and the second organic component in the organic complex layer is from 1:0.8 to 1:1.5.
[0025] In some embodiments, the weight-average molecular weight of the polyamine polymer and its derivatives in the organic composite layer is 1000-50000, for example, 2000, 4000, 6000, 7000, 8000, 8500, 9000, 9500, 10000, 10500, 11000, 11500, 12000, 12500, 13000, 13500, 14000, 14500, 1... The weight-average molecular weight of the polyamine polymer and its derivatives in the organic composite layer is 5000, 15500, 16000, 17000, 18000, 19000, 20000, 21000, 22000, 23000, 24000, 25000, 26000, 27000, 28000, 29000, 30000, 33000, 35000, 37000, 40000, 43000, 45000, 47000, or any value between them. In some embodiments, the weight-average molecular weight of the polyamine polymer and its derivatives in the organic composite layer is 5000-30000. In some embodiments, the weight-average molecular weight of the polyamine polymer and its derivatives in the organic composite layer is 8000-15000.
[0026] In some embodiments, the catalyst is an eggshell-type catalyst.
[0027] Secondly, this application provides a method for preparing a catalyst for hydrogenation and dehydrogenation of organic hydrogen storage liquids, comprising the following steps: S1: A first mixture comprising a metal oxide support, a first organic compound containing phenolic hydroxyl groups, a second organic compound containing amine groups, and a solvent is subjected to a hydrothermal reaction to obtain a hydrothermal reaction product; S2: The hydrothermal reaction products are processed to obtain a modified metal oxide support; S3: The active metal component is loaded onto the modified metal oxide support by impregnation to obtain the catalyst precursor; S4: The catalyst precursor from step S3 is reduced to obtain the catalyst.
[0028] In some embodiments, in step S3, the impregnation is selected from spray impregnation.
[0029] In some implementations, step S3 includes: S31: The impregnation solution including the active metal source is atomized and sprayed onto the modified metal oxide carrier; S32: The product from step S31 is subjected to a second drying process; S33: The dried product from step S32 is calcined to obtain the catalyst precursor.
[0030] In some embodiments, in step S31, the first drying is performed simultaneously with the spraying.
[0031] This application employs an atomized spraying method to atomize the impregnation solution containing active components into micron-sized droplets, which are then uniformly sprayed onto dynamically moving carrier particles. This achieves precise and controllable loading of the active components in terms of their position, size, and morphology on the carrier. Simultaneously, high-temperature rapid drying during spraying causes the solvent to evaporate quickly, significantly inhibiting the migration and aggregation of active components on the catalyst carrier. Furthermore, the instantaneous drying rate promotes rapid bonding between the active components and hydroxyl groups on the organic coating, forming a stronger anchoring effect. This prevents the active components from diffusing into the carrier and ensures they are promptly immobilized on the outer surface of the catalyst carrier, avoiding the agglomeration and growth of metal particles and improving the dispersion of the active components on the catalyst carrier.
[0032] In some embodiments, in step S31, a heat source gas is introduced for the first drying.
[0033] In some embodiments, the temperature of the hydrothermal reaction in step S1 is 100℃-150℃, for example, 105℃, 110℃, 115℃, 120℃, 125℃, 130℃, 135℃, 140℃, or 145℃. In some embodiments, the temperature of the hydrothermal reaction is 110℃-130℃.
[0034] In some embodiments, the hydrothermal reaction time in step S1 is 5h-20h, for example, 7h, 9h, 12h, 14h, 16h, or 18h. In some embodiments, the hydrothermal reaction time is 10h-15h.
[0035] In some embodiments, in step S1, the solvent is selected from one or more of C1-C4 alcohols (e.g., methanol, ethanol, or propanol) and water. In some embodiments, the solvent is selected from ethanol and / or water.
[0036] In some embodiments, in step S1, the first organic compound containing a phenolic hydroxyl group is selected from one or more polyphenolic compounds. In some embodiments, the polyphenolic compound is selected from one or more of tannic acid, 3,4,5-trihydroxybenzoic acid, pyrogallol, 2,2',4,4'-biphenyltetrol, black thorn bark condensed tannin, and lignin sulfonate. In some embodiments, the polyphenolic compound is selected from tannic acid.
[0037] In some embodiments, in step S1, the second organic compound containing an amine group is selected from one or more polyamine polymers. In some embodiments, the polyamine polymer is selected from one or more of polyethyleneimine, polyallylamine hydrochloride, polypropyleneimine, and aminolignin. In some embodiments, the polyamine polymer is selected from polyethyleneimine.
[0038] In some embodiments, in step S1, the second organic compound containing an amino group is selected from one or more alkylene polyamines. In some embodiments, the alkylene polyamine is selected from one or more alkylene polyamines having 2 to 6 carbon atoms. In some embodiments, the alkylene polyamine is selected from one or more of diethylenetriamine, triethylenetetramine, ethylenediamine, and hexamethylenediamine.
[0039] In some embodiments, in step S1, the metal oxide support is selected from one or more of alumina support, titanium oxide support, cerium oxide support, and porous molecular sieve support. In some embodiments, the porous molecular sieve support is selected from two-dimensional porous molecular sieve support. In some embodiments, the metal oxide support is selected from alumina support. In some embodiments, the metal oxide support is selected from porous molecular sieve support. In some embodiments, the porous molecular sieve support is selected from one or more of USY molecular sieve support, Beta molecular sieve support, and SBA-15 molecular sieve support.
[0040] In some embodiments, when the carrier is selected from alumina carrier, titanium oxide carrier, or cerium oxide carrier, preferably alumina carrier, the second organic compound containing an amine group is selected from one or more polyamine polymers.
[0041] In some embodiments, when the support is selected from porous molecular sieve supports, the second organic compound containing an amine group is selected from one or more alkylene polyamines.
[0042] In some embodiments, in step S1, the mass ratio of the first organic compound containing phenolic hydroxyl groups to the second organic compound containing amine groups is from 1:0.1 to 1:4, for example, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.55, 1:0.6, 1:0.65, 1:0.7, 1:0.75, 1:0.8, 1:0.83, 1:0.85, 1:0.87, 1:0.9, 1:0.93, 1:0.95, 1:0.97, 1:1, 1:1.03, 1:1.05, 1:1.07, 1:1.1, 1:1.13, 1:1.15, or 1:1. 17, 1:1.2, 1:1.23, 1:1.25, 1:1.27, 1:1.3, 1:1.33, 1:1.35, 1:1.37, 1:1.4, 1:1.43, 1:1.45, 1:1.47, 1:1.5, 1:1.53, 1:1.55, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9, 1:3, 1:3.3, 1:3.5, 1:3.7, or any value between them. In some embodiments, the mass ratio of the first organic compound containing a phenolic hydroxyl group to the second organic compound containing an amino group is from 1:0.5 to 1:3. In some embodiments, the mass ratio of the first organic compound containing phenolic hydroxyl groups to the second organic compound containing amine groups is from 1:0.8 to 1:1.5.
[0043] In some embodiments, the polyamine polymer has a weight-average molecular weight of 1000-50000, for example, 2000, 4000, 6000, 7000, 8000, 8500, 9000, 9500, 10000, 10500, 11000, 11500, 12000, 12500, 13000, 13500, 14000, 14500, 15000, 1... The weight-average molecular weight of the polyamine polymer is 5500, 16000, 17000, 18000, 19000, 20000, 21000, 22000, 23000, 24000, 25000, 26000, 27000, 28000, 29000, 30000, 33000, 35000, 37000, 40000, 43000, 45000, 47000, or any value between them. In some embodiments, the weight-average molecular weight of the polyamine polymer is 5000-30000. In some embodiments, the weight-average molecular weight of the polyamine polymer is 8000-15000.
[0044] In some embodiments, in step S1, the mass ratio of the first organic compound containing the phenolic hydroxyl group to the metal oxide support is from 0.001:1 to 0.08:1, for example, 0.005:1, 0.007:1, 0.01:1, 0.015:1, 0.02:1, 0.025:1, 0.027:1, 0.03:1, 0.031:1, 0.032:1, 0. The ratios are 0.033:1, 0.034:1, 0.035:1, 0.036:1, 0.037:1, 0.038:1, 0.039:1, 0.04:1, 0.041:1, 0.043:1, 0.045:1, 0.05:1, 0.055:1, 0.06:1, 0.065:1, 0.07:1, 0.075:1, or any value between them. In some embodiments, the mass ratio of the first organic compound containing the phenolic hydroxyl group to the metal oxide support is from 0.01:1 to 0.05:1. In some embodiments, the mass ratio of the first organic compound containing the phenolic hydroxyl group to the metal oxide support is from 0.03:1 to 0.04:1.
[0045] In some embodiments, in step S1, the mass ratio of the second organic compound containing the amine group to the metal oxide support is from 0.001:1 to 0.08:1, for example, 0.005:1, 0.007:1, 0.01:1, 0.015:1, 0.02:1, 0.025:1, 0.027:1, 0.03:1, 0.031:1, 0.032:1, 0.033:1, 0.034:1, 0.0 The ratios are 35:1, 0.036:1, 0.037:1, 0.038:1, 0.039:1, 0.04:1, 0.041:1, 0.042:1, 0.043:1, 0.044:1, 0.045:1, 0.046:1, 0.048:1, 0.05:1, 0.055:1, 0.06:1, 0.065:1, 0.07:1, 0.075:1, or any value between them. In some embodiments, the mass ratio of the amine-containing second organic compound to the metal oxide support is from 0.01:1 to 0.06:1. In some embodiments, the mass ratio of the amine-containing second organic compound to the metal oxide support is from 0.03:1 to 0.045:1.
[0046] In some embodiments, step S2 includes centrifugation, washing, and drying processes.
[0047] In some embodiments, in step S31, the active metal source is selected from one or more of a noble metal source and an optional non-noble metal source.
[0048] In some embodiments, in step S31, the noble metal source is selected from one or more of soluble noble metal salts and noble metal haloacids. In some embodiments, the noble metal in the noble metal source is selected from one or more of platinum, ruthenium, rhodium, and palladium. In some embodiments, the noble metal source is selected from one or more of chloroplatinic acid, chloropalladiumic acid, chlororutheniumic acid, chlororhodiumic acid, palladium nitrate, platinum nitrate, and palladium-rhodium nitrate. In some embodiments, the noble metal source is selected from chloroplatinic acid.
[0049] In some embodiments, in step S31, the non-precious metal source is selected from one or more soluble non-precious metal salts. In some embodiments, the non-precious metal source is selected from one or more non-precious metal nitrates, non-precious metal sulfates, and non-precious metal hydrochlorides. In some embodiments, the non-precious metal in the non-precious metal source is selected from one or more of nickel, cobalt, copper, iron, and molybdenum. In some embodiments, the non-precious metal source is selected from one or more of nickel nitrate, nickel sulfate, nickel acetate, nickel chloride, cobalt nitrate, cobalt sulfate, cobalt acetate, cobalt chloride, copper nitrate, copper sulfate, copper acetate, copper chloride, ferric nitrate, ferric sulfate, ferric acetate, ferric chloride, molybdenum nitrate, molybdenum sulfate, molybdenum acetate, and molybdenum chloride. In some embodiments, the non-precious metal source is selected from one or more of nickel nitrate, nickel sulfate, nickel acetate, and nickel chloride.
[0050] In some embodiments, in step S31, the mass content of the active metal source in the impregnation solution, based on the mass of the metal oxide support and calculated by metal element, is 0.01%-15%, for example, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.3%, 3.5%, 3.7%, 4.0%, 4.3%, 4.5%, 4.7%, 5.0%, 5.3%, 5.5%, 5.7%, 6.0%, 6.3%, 6.5%, 6.7%, 7.0%, 7.3%, 7.5%, 7.7%, 8.0%, 8.3%, 8.5%, 9.0%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, or any value between them. In some embodiments, the mass content of the active metal source, calculated by metal element, is 0.5%-10%. In some embodiments, the active metal source has a mass content of 3%-8% based on metal elements.
[0051] In some embodiments, in step S31, the mass content of the precious metal source in the impregnation solution, calculated as precious metal elements, is 0.1%-1.0%, for example, 0.15%, 0.2%, 0.23%, 0.25%, 0.27%, 0.3%, 0.33%, 0.35%, 0.37%, 0.4%, 0.43%, 0.45%, 0.47%, 0.5%, 0.53%, 0.55%, 0.57%, 0.6%, 0.63%, 0.65%, 0.67%, 0.7%, 0.73%, 0.75%, 0.77%, 0.8%, 0.83%, 0.85%, 0.9%, 0.95%, or any value between them. In some embodiments, the mass content of the precious metal source, calculated as precious metal elements, is 0.2%-0.8%.
[0052] In some embodiments, in step S31, the mass content of the non-precious metal source in the impregnation solution, calculated as non-precious metal elements, is 1%-15%, for example, 1.5%, 2.0%, 2.5%, 3.0%, 3.3%, 3.5%, 3.7%, 4.0%, 4.3%, 4.5%, 4.7%, 5.0%, 5.3%, 5.5%, 5.7%, 6.0%, 6.3%, 6.5%, 6.7%, 7.0%, 7.3%, 7.5%, 7.7%, 8.0%, 8.3%, 8.5%, 9.0%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, or any value between them. In some embodiments, the mass content of the non-precious metal source, calculated as non-precious metal elements, is 3%-10%.
[0053] In some embodiments, in step S31, the spraying temperature is 40°C-80°C, for example, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, or 75°C. In some embodiments, in step S31, the spraying temperature is 50°C-70°C.
[0054] In some embodiments, in step S31, the temperature of the first drying is 100℃-150℃, for example, 105℃, 110℃, 115℃, 120℃, 125℃, 130℃, 135℃, 140℃, or 145℃. In some embodiments, in step S31, the temperature of the first drying is 110℃-130℃.
[0055] In some embodiments, in step S31, the temperature of the heat source gas is 120°C-180°C, for example, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C or 175°C.
[0056] In some embodiments, in step S31, the gas velocity of the heat source gas is 5 h⁻¹. -1 -1200h -1 For example, 50h -1 100h -1 150h -1 200h -1 250h -1 300h -1 450h -1 400h -1 430h -1 450h -1 470h -1 500h -1 530h -1 550h -1 570h -1 600h -1 630h -1 650h -1 670h -1 700h -1 730h -1 750h -1 770h -1 800h -1 830h -1 850h -1 900h -1 950h -1 1000h -1 1050h -1 1100h -1 1150h -1 Or any value in between. In some embodiments, the inlet space velocity of the heat source gas is 200 h⁻¹. -1 -1000h -1 In some embodiments, the gas velocity of the heat source gas is 400 h⁻¹. -1 -800h -1 .
[0057] In some embodiments, in step S31, the heat source gas is selected from one or more of hot air, nitrogen, argon, and carbon dioxide.
[0058] In some embodiments, in step S32, the temperature of the second drying is 100°C-150°C, for example, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, or 145°C. In some embodiments, in step S32, the temperature of the second drying is 110°C-130°C.
[0059] In some embodiments, in step S32, a heat source gas is introduced for a second drying process. In some embodiments, the heat source gas in step S32 is the same as that in step S31, for example, selected from one or more of hot air, nitrogen, argon, and carbon dioxide.
[0060] In some implementations, in step S32, the space velocity of the heat source gas is the same as that of the heat source gas in step S31, for example, 5 h. -1 -1200h -1 .
[0061] In some embodiments, after the second drying, the moisture content of the product from step S31 is less than or equal to 0.3%.
[0062] In some embodiments, the calcination temperature in step S33 is 400°C-700°C, for example, 450°C, 500°C, 550°C, 600°C, or 650°C. In some embodiments, the calcination temperature is 500°C-600°C.
[0063] In some embodiments, the roasting time in step S33 is 1h-10h, for example, 2h, 3h, 4h, 5h, 6h, 7h, 8h or 9h. In some embodiments, the roasting time in step S33 is 3h-6h.
[0064] In some embodiments, the reduction treatment temperature in step S4 is 200℃-500℃, for example, 250℃, 300℃, 350℃, 400℃, or 450℃. In some embodiments, the reduction treatment temperature is 300℃-400℃.
[0065] In some embodiments, the reduction process in step S4 takes 1-10 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, or 9 hours. In some embodiments, the reduction process takes 3-6 hours.
[0066] In some embodiments, in step S4, the reduction process is carried out in the presence of a reducing gas. In some embodiments, the reducing gas is selected from hydrogen. In some embodiments, the space velocity of the reducing gas is 5 h⁻¹. -1 -15h -1 For example, 6h -1 7h -1 8h -1 9h -1 10h -1 11h -1 12h -1 13h -1 or 14h -1 .
[0067] In some embodiments, the preparation method includes the following specific steps: (1) A certain amount of alumina carrier, anhydrous ethanol, tannic acid and polyethyleneimine were placed in a beaker and sonicated for 2 hours. Then, the mixture was transferred to a stainless steel high-pressure reactor and hydrothermally reacted at 120°C for 12 hours. After the reaction was completed, the mixture was centrifuged and washed to obtain tannic acid-modified alumina carrier. (2) The impregnation solution is uniformly dispersed on the surface of the catalyst support and dried rapidly by spraying and fast drying, so that the active components are quickly fixed on the surface of the catalyst support.
[0068] Thirdly, this application provides an application of the catalyst described in the first aspect or the catalyst prepared by the preparation method described in the second aspect in the hydrogenation and dehydrogenation of organic hydrogen storage liquids.
[0069] In some embodiments, the organic hydrogen storage liquid is selected from one or more of dibenzyltoluene, benzyltoluene, and toluene.
[0070] Fourthly, this application provides a method for hydrogenation and dehydrogenation of organic hydrogen storage liquids, which includes alternating hydrogenation and dehydrogenation reactions of the organic hydrogen storage liquids in the presence of a catalyst to achieve hydrogen storage and release.
[0071] In some embodiments, the organic hydrogen storage liquid is selected from one or more of dibenzyltoluene, benzyltoluene, and toluene.
[0072] In some embodiments, the hydrogenation reaction is carried out under the following conditions: a reaction temperature of 200-260°C and a feed space velocity of 0.2 h⁻¹. -1 -1h -1 The feed hydrogen-to-oil ratio is (1000-5000):1.
[0073] In some embodiments, the reaction temperature of the hydrogenation reaction is 210°C, 220°C, 230°C, 240°C, or 250°C.
[0074] In some embodiments, the feed space velocity for the hydrogenation reaction is 0.3 h⁻¹. -1 0.4h -1 0.5h -1 0.6h -1 0.7h -1 0.8h -1 or 0.9h -1 .
[0075] In some embodiments, the hydrogen-to-oil ratio in the feed for the hydrogenation reaction is 1500:1, 2000:1, 2500:1, 3000:1, 3500:1, 4000:1, or 4500:1.
[0076] In some embodiments, the dehydrogenation reaction is carried out under the following conditions: a reaction temperature of 300°C-400°C and a feed space velocity of 1 h⁻¹. -1 -5h -1 The feed hydrogen-to-oil ratio is (100-800):1.
[0077] In some embodiments, the dehydrogenation reaction is carried out at a temperature of 320°C, 340°C, 3500°C, 360°C, or 380°C.
[0078] In some embodiments, the feed space velocity for the dehydrogenation reaction is 1.5 h⁻¹. -1 2h -1 2.5h -1 3h -1 3.5h -1 4h -1 or 4.5h -1 .
[0079] In some embodiments, the feed hydrogen-to-oil ratio for the dehydrogenation reaction is 200:1, 300:1, 400:1, 500:1, 600:1, or 700:1.
[0080] The beneficial technical effects of this application are as follows: (1) This application forms a coating on the surface of the catalyst support by chemical modification. The organic functional groups on the coating greatly enhance the anchoring effect on the active components and establish strong chemical bonds between the support and the metal active components, thereby inhibiting the migration, aggregation and excessive growth of the active components on the catalyst, and thus obtaining metal nanoparticles with smaller size and more uniform dispersion.
[0081] (2) This application achieves instantaneous and uniform liquid-solid contact by combining spray impregnation and rapid drying, avoiding excessively high local impregnation concentration. At the same time, rapid drying can quickly remove the solvent, destroy the conditions for the generation of capillary forces that lead to the migration of active components, greatly shorten the migration of active components on the catalyst, and fix them at the initial contact position before migration, avoiding the agglomeration and growth of metal particles and improving the dispersion of active components on the catalyst support. Detailed Implementation
[0082] Unless otherwise stated, all figures used in this application to indicate content, concentration, proportion, weight, particle size, percentage, technical effect, etc., should in any case be understood to be modified by the terms “about” or “approximately”. Therefore, unless indicated to the contrary, the numerical parameters listed in this application are approximate values.
[0083] When used in this application, the expression "A and / or B" includes three cases: (1) A; (2) B; and (3) A and B. The expression "A, B and / or C" includes seven cases: (1) A; (2) B; (3) C; (4) A and B; (5) A and C; (6) B and C; and (7) A, B and C. The meanings of similar expressions can be deduced by analogy.
[0084] When used in this application, the term "independently" means that multiple events do not affect each other. For example, "X and Y are independently selected from any one of a, b, c, d, e, f, g" means that X can be any one of a, b, c, d, e, f, g, and Y can also be any one of a, b, c, d, e, f, g. The selection of X and the selection of Y can be the same or different, and they do not interfere with each other.
[0085] As used in this application, the terms "comprising" and "including" mean that other elements are not excluded in addition to the elements listed.
[0086] The following describes exemplary embodiments of this application, including various details of the embodiments to aid understanding. It should be understood that these are merely exemplary and are in no way intended to limit the scope of protection of this application. The scope of protection of this application is defined only by the claims. Therefore, those skilled in the art will recognize that various changes and modifications can be made to the embodiments described herein without departing from the scope of this application. Similarly, for clarity and brevity, descriptions of well-known functions and structures are omitted in the following description.
[0087] Unless otherwise stated, all reagents and instruments used in the following examples are commercially available products. Experiments were conducted under standard conditions or conditions recommended by the manufacturer, unless otherwise stated.
[0088] Example 1 Step 1: Place 100g of commercial alumina support in a beaker, add 50mL of anhydrous ethanol, 3.6g of tannic acid, 3.6g of polyethyleneimine (Mw=10000), and 56mL of deionized water, and then sonicate for 2 hours. Next, transfer the mixture to a stainless steel high-pressure reactor and hydrothermally react at 120℃ for 12 hours. After the reaction, collect the solid product by centrifugation, wash it three times with ethanol and deionized water, and finally freeze-dry it to obtain the modified catalyst support.
[0089] Step 2: Place 1.578g of chloroplatinic acid, 24.7g of nickel nitrate, and 106g of deionized water in a beaker and stir until completely dissolved to obtain the impregnation solution.
[0090] Step 3: Place the carrier from Step 1 into the coating machine, and evenly spray the impregnation solution from Step 2 (impregnation solution temperature is 60℃) onto the carrier from Step 1 through an atomizing nozzle, while simultaneously introducing 120℃ hot air (GHSV=600h). -1 After the spraying process is completed, hot air at 120°C is continuously introduced (GHSV=600h). -1 The material was dried to a moisture content of <0.3%, and then calcined in a muffle furnace at 550°C for 4 hours to obtain the catalyst precursor.
[0091] Step 4: The catalyst from Step 3 is reduced to obtain the final catalyst. The reduction temperature is 350℃, the reduction time is 4 hours, and the reduction space velocity (GHSV) is 8 hours. -1 The reducing atmosphere is hydrogen.
[0092] The catalysts obtained above were subjected to structural characterization tests, and the results are detailed in Table 1.
[0093] Example 2 Step 1 differs from Example 1 in that the mass of tannic acid is 4.8g and the mass of polyethyleneimine is 2.4g, while the rest is the same as in Example 1.
[0094] Step 2 is the same as in Example 1.
[0095] Step 3 is the same as in Example 1.
[0096] Step 4 is the same as in Example 1.
[0097] The catalysts obtained above were subjected to structural characterization tests, and the results are detailed in Table 1.
[0098] Example 3 Step 1 differs from Example 1 in that the mass of tannic acid is 3.0g and the mass of polyethyleneimine is 4.2g, while the rest is the same as in Example 1.
[0099] Step 2 is the same as in Example 1.
[0100] Step 3 is the same as in Example 1.
[0101] Step 4 is the same as in Example 1.
[0102] The catalysts obtained above were subjected to structural characterization tests, and the results are detailed in Table 1.
[0103] Example 4 Step 1 differs from Example 1 in that the mass of tannic acid is 2.4g and the mass of polyethyleneimine is 4.8g, while the rest is the same as in Example 1.
[0104] Step 2 is the same as in Example 1.
[0105] Step 3 is the same as in Example 1.
[0106] Step 4 is the same as in Example 1.
[0107] The catalysts obtained above were subjected to structural characterization tests, and the results are detailed in Table 1.
[0108] Example 5 Step 1 differs from Example 1 in that the mass of tannic acid is 1.8g and the mass of polyethyleneimine is 5.4g, while the rest is the same as in Example 1.
[0109] Step 2 is the same as in Example 1.
[0110] Step 3 is the same as in Example 1.
[0111] Step 4 is the same as in Example 1.
[0112] The catalysts obtained above were subjected to structural characterization tests, and the results are detailed in Table 1.
[0113] Example 6 Step 1 differs from Example 1 in that the weight-average molecular weight of polyethyleneimine is 1800, while the rest is the same as in Example 1.
[0114] Step 2 is the same as in Example 1.
[0115] Step 3 is the same as in Example 1.
[0116] Step 4 is the same as in Example 1.
[0117] The catalysts obtained above were subjected to structural characterization tests, and the results are detailed in Table 1.
[0118] Example 7 Step 1 differs from Example 1 in that the weight-average molecular weight of polyethyleneimine is 25,000, while the rest is the same as in Example 1.
[0119] Step 2 is the same as in Example 1.
[0120] Step 3 is the same as in Example 1.
[0121] Step 4 is the same as in Example 1.
[0122] The catalysts obtained above were subjected to structural characterization tests, and the results are detailed in Table 1.
[0123] Example 8 Step 1 is the same as in Example 1.
[0124] Step 2 is the same as in Example 1.
[0125] Step 3, the difference from Example 1 is that the air velocity of the introduced hot air is: GHSV = 200h -1 The rest is the same as in Example 1.
[0126] Step 4 is the same as in Example 1.
[0127] The catalysts obtained above were subjected to structural characterization tests, and the results are detailed in Table 1.
[0128] Example 9 Step 1 is the same as in Example 1.
[0129] Step 2 is the same as in Example 1.
[0130] Step 3, the difference from Example 1 is that the air velocity of the introduced hot air is: GHSV = 800h -1 The rest is the same as in Example 1.
[0131] Step 4 is the same as in Example 1.
[0132] The catalysts obtained above were subjected to structural characterization tests, and the results are detailed in Table 1.
[0133] Example 10 Step 1 is the same as in Example 1.
[0134] Step 2 is the same as in Example 1.
[0135] Step 3: Place the carrier from Step 1 into the coating machine, and evenly spray the impregnation solution from Step 2 onto the carrier from Step 1 through an atomizing nozzle. After spraying, introduce 120℃ hot air (GHSV=600h). -1 The material was dried to a moisture content of <0.3%, and then calcined in a muffle furnace at 550°C for 4 hours to obtain the catalyst precursor.
[0136] Step 4 is the same as in Example 1.
[0137] The catalysts obtained above were subjected to structural characterization tests, and the results are detailed in Table 1.
[0138] Example 11 Step 1 differs from Example 1 in that the same mass of diethylenetriamine is used instead of polyethyleneimine, and the same mass of SBA-15 molecular sieve is used instead of commercial alumina support. The rest is the same as in Example 1.
[0139] Step 2 is the same as in Example 1.
[0140] Step 3 is the same as in Example 1.
[0141] Step 4 is the same as in Example 1.
[0142] The catalysts obtained above were subjected to structural characterization tests, and the results are detailed in Table 1.
[0143] Comparative Example 1 Step 1 differs from Example 1 in that the mass of tannic acid is 7.2g and the mass of polyethyleneimine is 0g, while the rest is the same as in Example 1.
[0144] Step 2 is the same as in Example 1.
[0145] Step 3 is the same as in Example 1.
[0146] Step 4 is the same as in Example 1.
[0147] The catalysts obtained above were subjected to structural characterization tests, and the results are detailed in Table 1.
[0148] Comparative Example 2 Step 1 differs from Example 1 in that the mass of tannic acid is 0g and the mass of polyethyleneimine is 7.2g, while the rest is the same as in Example 1.
[0149] Step 2 is the same as in Example 1.
[0150] Step 3 is the same as in Example 1.
[0151] Step 4 is the same as in Example 1.
[0152] The catalysts obtained above were subjected to structural characterization tests, and the results are detailed in Table 1.
[0153] Characterization test 1. Metal content test Inductively coupled plasma mass spectrometry (ICP-MS) was used to determine the content of active components in the catalyst. After the reduced catalyst was ground uniformly, it was first pre-digested with aqua regia, followed by further digestion at elevated temperature. After washing and making up to 50 mL, it was diluted 10 times for measurement. A solution of active components with known concentration was prepared using deionized water, and then a standard curve was determined.
[0154] 2. Platinum Dispersion Test The dispersion of the analyte metal was determined using CO chemisorption. First, the catalyst was weighed into a U-shaped quartz tube and heated to 350 °C at a rate of 10 °C / min, followed by reduction with H₂ for 4 h. After cooling to 50 °C, excess H₂ was purged with pure He. Once the baseline stabilized, a 10% CO / He mixture was introduced, and pulse signals were recorded every 5 min using a thermal conductivity detector (TCD). After adsorption saturation, the total CO adsorption was calculated. The dispersion of the analyte metal was then determined based on the CO adsorption amount.
[0155] Table 1
[0156] Performance testing The catalysts prepared in the above examples and comparative examples were subjected to performance tests and compared with fresh catalysts. The dehydrogenation reaction of perhydrodibenzyltoluene was carried out under the following experimental conditions: dehydrogenation temperature = 325℃, feed space velocity = 2h. -1 (Heavy hourly space velocity), feed hydrogen-to-oil ratio = 2000:1, dehydrogenation performance is shown in Table 2 below.
[0157] Table 2
[0158] The comparison between Example 1 and Comparative Examples 1 and 2 in the table above shows that the phenolic hydroxyl groups rich in tannic acid form an imine / hydrogen bond crosslinking hybrid network with the amino groups contained in polyethyleneimine. This network can efficiently bind the metal active components, inhibit the local enrichment of active components during the spraying process, improve the dispersion of active components, and ultimately enhance both the catalyst activity and stability. Based on the data from Examples 1-5 in the table above, it can be seen that a balanced ratio of tannic acid and polyethyleneimine results in the highest dispersion, conversion rate, and selectivity of the active component. Excessive amounts of tannic acid or polyethyleneimine can lead to crystal agglomeration and growth, reduced dispersion, and consequently, lower initial conversion rate and selectivity.
[0159] From the data in Examples 1, 6, and 7 above, it can be concluded that: small-molecule polyethyleneimine has a high initial dehydrogenation conversion rate, but after high-temperature operation, the active components rapidly aggregate and grow, resulting in a rapid decrease in catalyst activity. Although large-molecule polyethyleneimine catalysts have relatively good stability, they are prone to clogging pores, hindering material diffusion, and their dehydrogenation conversion rate and selectivity are significantly lower than those of medium-molecule polyethyleneimine at the same temperature.
[0160] The main difference between Example 1 and Examples 8-9 lies in the space velocity of the hot air introduced during the simultaneous spraying and drying process. Low space velocity drying, while resulting in moderate dispersion of the active component, reduces the ligand chelation and binding capacity, making it prone to sintering and agglomeration, leading to a rapid decrease in catalyst activity. High space velocity drying, with its high airflow rate and rapid, instantaneous dehydration, significantly reduces the dispersion of the active component, resulting in a decrease in effective active sites for the same active component loading.
[0161] Compared to Example 1, Example 10 uses a conventional method of first spraying and then drying. This method causes the active components of the catalyst to easily agglomerate during calcination, resulting in a relatively lower dispersion. Furthermore, the grown active components can exacerbate side reactions, reduce catalyst selectivity, and cause the catalyst activity to decay more rapidly.
[0162] While some exemplary embodiments of this application have been described and illustrated, this application is not limited to the disclosed embodiments. Rather, those skilled in the art will recognize that modifications and changes may be made to the described embodiments without departing from the spirit and scope of this application as described in the appended claims.
Claims
1. A catalyst for hydrogenation and dehydrogenation of organic hydrogen storage liquids, comprising a metal oxide support, an organic composite layer supported on the metal oxide support, and a metal active component bonded to the organic composite layer. in, The organic composite layer comprises a first organic component containing phenolic hydroxyl groups and a second organic component containing amine groups.
2. The catalyst according to claim 1, characterized in that, The first organic component is selected from one or more polyphenolic compounds and their derivatives. Preferably, the polyphenolic compounds are selected from one or more of tannic acid, 3,4,5-trihydroxybenzoic acid, pyrogallol, 2,2',4,4'-biphenyltetrol, black thorn bark condensed tannin, and lignin sulfonate; and / or The second organic component is selected from one or more of polyamine polymers and their derivatives, and alkylene polyamines and their derivatives. Preferably, the polyamine polymer is selected from one or more of polyethyleneimine, polyallylamine hydrochloride, polypropyleneimine, and aminolignin. Preferably, the alkylene polyamine is selected from one or more of alkylene polyamines having 2 to 6 carbon atoms, and more preferably from one or more of diethylenetriamine, triethylenetetramine, ethylenediamine, and hexamethylenediamine; and / or The metal oxide support is selected from one or more of alumina support, titanium oxide support, cerium oxide support, and porous molecular sieve support, preferably from alumina support and / or porous molecular sieve support, more preferably from one or more of USY molecular sieve support, Beta molecular sieve support, and SBA-15 molecular sieve support; and / or The active metal component includes one or more noble metals and optional non-noble metals. Preferably, the precious metal is selected from one or more of platinum, ruthenium, rhodium, and palladium. Preferably, the non-precious metal is selected from one or more of nickel, cobalt, copper, iron, and molybdenum.
3. The catalyst according to any one of claims 1 or 2, characterized in that, The organic composite layer includes a three-dimensional network formed by the self-assembly of the first organic component and the second organic component. Preferably, the three-dimensional network is formed by the self-assembly of the first organic component and the second organic component through one or more of hydrogen bonding, lone pair electron coordination and oxygen coordination chelation. Preferably, the three-dimensional network is selected from organic amine networks and / or metal polyphenol networks; Preferably, the first organic component is bridged and anchored to the surface of the metal oxide carrier via the second organic component; and / or The active metal component and the organic composite layer are bonded together by chemical bonds, preferably through metal-phenolic hydroxyl coordination bonds.
4. The catalyst according to any one of claims 1-3, characterized in that, Based on the mass of the catalyst, the mass content of the metal active component is 0.01%-15wt%, preferably 0.5%-10%, and more preferably 3%-8%; Preferably, the precious metal content is 0.1%-1.0% by mass, more preferably 0.2%-0.8%, and the non-precious metal content is 1%-15% by mass, more preferably 3%-10%; and / or The mass ratio of the first organic component to the second organic component in the organic complex layer is 1:0.1 to 1:4, preferably 1:0.5 to 1:3, more preferably 1:0.8 to 1:1.5; and / or The weight-average molecular weight of polyamine polymers and their derivatives is 1,000-50,000, preferably 5,000-30,000, and more preferably 8,000-15,000.
5. A method for preparing a catalyst for hydrogenation and dehydrogenation of organic hydrogen storage liquids, comprising the following steps: S1: A first mixture comprising a metal oxide support, a first organic compound containing phenolic hydroxyl groups, a second organic compound containing amine groups, and a solvent is subjected to a hydrothermal reaction to obtain a hydrothermal reaction product; S2: The hydrothermal reaction products are processed to obtain a modified metal oxide support; S3: The active metal component is loaded onto the modified metal oxide support by impregnation to obtain the catalyst precursor. Preferably, the impregnation is selected from spray impregnation. S4: The catalyst precursor from step S3 is reduced to obtain the catalyst.
6. The preparation method according to claim 5, characterized in that, Step S3 includes: S31: The impregnation solution including the active metal source is atomized and sprayed onto the modified metal oxide carrier. Preferably, the first drying is performed at the same time as the spraying, and more preferably, a heat source gas is introduced to perform the first drying. S32: The product from step S31 is subjected to a second drying process; S33: The dried product from step S32 is calcined to obtain the catalyst precursor.
7. The preparation method according to claim 5 or 6, characterized in that, In step S1, the temperature of the hydrothermal reaction is 100℃-150℃, preferably 110℃-130℃; and / or The hydrothermal reaction time is 5h-20h, preferably 10h-15h; and / or The solvent is selected from one or more C1-C4 alcohols and water, preferably from ethanol and / or water; and / or The first organic compound containing a phenolic hydroxyl group is selected from one or more polyphenolic compounds, preferably, the polyphenolic compound is selected from one or more of tannic acid, 3,4,5-trihydroxybenzoic acid, pyrogallol, 2,2',4,4'-biphenyltetrol, black thorn bark condensed tannin, and lignin sulfonate; and / or The second organic compound containing an amine group is selected from one or more of polyamine polymers and alkylene polyamines. Preferably, the polyamine polymer is selected from one or more of polyethyleneimine, polyallylamine hydrochloride, polypropyleneimine, diethylenetriamine, triethylenetetramine, ethylenediamine, hexamethylenediamine, and aminolignin. Preferably, the alkylene polyamine is selected from one or more of alkylene polyamines having 2 to 6 carbon atoms, and more preferably from one or more of diethylenetriamine, triethylenetetramine, ethylenediamine, and hexamethylenediamine; and / or The metal oxide support is selected from one or more of alumina support, titanium oxide support, cerium oxide support, and porous molecular sieve support, preferably from alumina support and / or porous molecular sieve support, more preferably from one or more of USY molecular sieve support, Beta molecular sieve support, and SBA-15 molecular sieve support; and / or The mass ratio of the first organic compound containing a phenolic hydroxyl group to the second organic compound containing an amino group is 1:0.1 to 1:4, preferably 1:0.5 to 1:3, more preferably 1:0.8 to 1:1.5; and / or The polyamine polymers have a weight-average molecular weight of 1,000-50,000, preferably 5,000-30,000, and more preferably 8,000-15,000; and / or The mass ratio of the first organic compound containing phenolic hydroxyl groups to the metal oxide support is 0.001:1 to 0.08:1, preferably 0.01:1 to 0.05:1, more preferably 0.03:1 to 0.04:1; and / or The mass ratio of the second organic compound containing an amine group to the metal oxide support is 0.001:1 to 0.08:1, preferably 0.01:1 to 0.06:1, more preferably 0.03:1 to 0.045:1; and / or In step S2, the process includes centrifugation, washing, and drying.
8. The preparation method according to any one of claims 6 or 7, characterized in that, In step S31, the active metal source is selected from one or more of noble metal sources and optional non-noble metal sources; Preferably, the noble metal source is selected from one or more of soluble noble metal salts and noble metal halo acids, and more preferably from one or more of chloroplatinic acid, chloropalladiumic acid, chlororuthenic acid, chlororhodiumic acid, palladium nitrate, platinum nitrate, and palladium rhodium nitrate. Preferably, the non-precious metal source is selected from one or more soluble non-precious metal salts, more preferably from one or more non-precious metal nitrates, non-precious metal sulfates, and non-precious metal hydrochlorides; and more preferably, the non-precious metal is selected from one or more of nickel, cobalt, copper, iron, and molybdenum; and / or In the impregnation solution, based on the mass of the metal oxide support, the active metal source, calculated by metal element, has a mass content of 0.01%-15 wt%, preferably 0.5%-10%, more preferably 3%-8%, preferably, calculated by precious metal element, the precious metal source has a mass content of 0.1%-1.0%, preferably 0.2%-0.8%, and calculated by non-precious metal element, the non-precious metal source has a mass content of 1%-15%, preferably 3%-10%; and / or The spraying temperature is 40℃-80℃, preferably 50℃-70℃; and / or The temperature of the first drying is 100℃-150℃, preferably 110℃-130℃; and / or The temperature of the heat source gas is 120℃-180℃; and / or The gas velocity of the heat source gas is 5 h⁻¹. -1 -1200h -1 Preferably 200h -1 -1000h -1 More preferably 400h -1 -800h -1 ; and / or The heat source gas is selected from one or more of hot air, nitrogen, argon, and carbon dioxide; and / or In step S32, the temperature for the second drying is 100℃-150℃, preferably 110℃-130℃; and / or After the second drying, the moisture content of the product from step S31 is less than or equal to 0.3%; and / or In step S33, the calcination temperature is 400℃-700℃, preferably 500℃-600℃; and / or In step S4, the reduction treatment temperature is 200℃-500℃, preferably 300℃-400℃; and / or The reduction treatment time is 1 hour to 10 hours, preferably 3 hours to 6 hours; and / or The reduction process is carried out in the presence of a reducing gas, preferably hydrogen, and / or the space velocity of the reducing gas is 5 h⁻¹. -1 -15h -1 .
9. The application of a catalyst according to any one of claims 1-4 or a catalyst prepared by any one of claims 5-8 in the hydrogenation and dehydrogenation of organic hydrogen storage liquids; Preferably, the organic hydrogen storage liquid is selected from one or more of dibenzyltoluene, benzyltoluene, and toluene.
10. A method for hydrogenation and dehydrogenation of an organic hydrogen storage liquid, comprising alternating hydrogenation and dehydrogenation reactions of the organic hydrogen storage liquid in the presence of a catalyst to achieve hydrogen storage and release; Preferably, the organic hydrogen storage liquid is selected from one or more of dibenzyltoluene, benzyltoluene, and toluene; Preferably, the conditions for the hydrogenation reaction are: a reaction temperature of 200-260°C and a feed space velocity of 0.2 h⁻¹. -1 -1h -1 The feed hydrogen-to-oil ratio is (1000-5000):1; Preferably, the conditions for the dehydrogenation reaction are: a reaction temperature of 300℃-400℃ and a feed space velocity of 1 h⁻¹. -1 -5h -1 The feed hydrogen-to-oil ratio is (100-800):1.
Citation Information
Patent Citations
A highly active alumina-supported platinum catalyst, its preparation method and application
CN113368897B
